2020
DOI: 10.1155/2020/7351716
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Associated with Dietetic Advice Reduces Inflammatory Biomarkers in the Elderly

Abstract: Aging is a biological process during which chronic low-grade inflammation is present due to changes in the immune system of the elderly. The main objective of this study is to evaluate the effects of resistance training associated with dietary advice on chronic inflammation in the elderly. We conducted a prospective intervention study in which we evaluated anthropometric parameters and inflammatory biomarkers (CRP, IL-8, CCL-2, and leptin) in 40 elderly people before and after long-term progressive resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Aging is a physiological process known to produce changes in body composition, affecting the musculature and decreasing muscle volume and strength (Planella-Farrugia et al, 2019). In addition, resistance training and dietary guidance, especially foods with anti-inflammatory and antioxidant properties, can inhibit aging by reducing waist circumference and body fat percentage and increasing arm circumference and calf circumference (Lopes et al, 2020). Specific markers may be utilized to assess for malnutrition as such.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is a physiological process known to produce changes in body composition, affecting the musculature and decreasing muscle volume and strength (Planella-Farrugia et al, 2019). In addition, resistance training and dietary guidance, especially foods with anti-inflammatory and antioxidant properties, can inhibit aging by reducing waist circumference and body fat percentage and increasing arm circumference and calf circumference (Lopes et al, 2020). Specific markers may be utilized to assess for malnutrition as such.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training can help reduce chronic inflammation in the elderly, especially when combined with dietary advice [ 22 ]. However, the available studies have not addressed a possible concomitant influence of habitual diet quality and other lifestyle factors on inflammatory profile [ 17 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that a resistance exercise program of long duration and progressive intensity associated with dietary guidance is able to reduce chronic inflammation in the elderly [ 22 ]. However, this current study clarifies that groups with poor dietary quality benefit most from this combination of exercise and nutritional counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms underlying this phenomenon require further exploration. For example, physical exercise is effective in improving leptin resistance and improving leptin resistance through resistance training has been a hot research topic in recent years ( Lopes et al., 2020 ; Rios et al., 2021 ). In addition, the circadian clock plays an important role in leptin secretion and leptin resistance ( Russo et al., 2021 ; Adhikary et al., 2016 ).…”
Section: Leptin Resistancementioning
confidence: 99%